2012
DOI: 10.3109/00016357.2012.680909
|View full text |Cite
|
Sign up to set email alerts
|

Guided tissue regeneration using rigid absorbable membranes in the dog model of chronic furcation defect

Abstract: Although partial regeneration of the defect was observed, it was limited by wound contamination. Consequently, rigid absorbable membranes made of HA and PHB failed to improve the regeneration of class II furcation defects in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…While the characteristics of bioabsorbable barriers accelerate their biodegradation, negative outcomes may also be observed for the exposure of absorbable membranes to the oral cavity . Recently, Carlo Reis et al developed an absorbable but rigid membranes (made of hydroxyapatite and polyhydroxybutyrate matrix) aiming at preventing their collapse into the defect during periodontal regeneration of class II furcation defects in dogs. In line with the previous mentioned studies, these authors observed that although partial regeneration of the defect has been achieved, it was limited by membrane exposure and wound contamination.…”
Section: Eptfe Membrane Exposure/retrieval Timementioning
confidence: 89%
“…While the characteristics of bioabsorbable barriers accelerate their biodegradation, negative outcomes may also be observed for the exposure of absorbable membranes to the oral cavity . Recently, Carlo Reis et al developed an absorbable but rigid membranes (made of hydroxyapatite and polyhydroxybutyrate matrix) aiming at preventing their collapse into the defect during periodontal regeneration of class II furcation defects in dogs. In line with the previous mentioned studies, these authors observed that although partial regeneration of the defect has been achieved, it was limited by membrane exposure and wound contamination.…”
Section: Eptfe Membrane Exposure/retrieval Timementioning
confidence: 89%
“…The experimental model is commonly used in much of the literature, as Chantarawaratit et al reported that acemannan significantly accelerates new alveolar bone, cementum and periodontal ligament formation in class II furcation defects [37]. Reis et al reported that rigid membranes made of 25% or 35% hydroxyapatite and polyhydroxybutyrate partially improved the regeneration of class II furcation defects in dogs, but an inflammatory infiltrate was also observed in the dense connective tissue [38]. Figures 7 and 8 show that in our study, the percentage of new bone formation in the Col/BG/CS group was higher than that of the control group at 30 and 60 d, and bone matrix protein (OCN) was presented in the newly formed bone.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies providing data on the effect of OFD in animal class II furcation defects were identified (Table 4) [39,53,55,57,69,71,75,76,78,99,101,102,112,114,115,118,120]. The majority of the studies (i.e., 11 out 16) showed long junctional epithelium, whereas new cementum, PDL and/or new alveolar bone were observed only in a few cases at the apical limit of the defect [28-34, 36, 38, 39, 43].…”
Section: Animal Class II Furcation Defects Treated With Ofdmentioning
confidence: 99%
“…Fourteen studies providing data on the effect of the use of GTR in animal class II furcation defects were identified (Table 8). Six studies used resobable membranes [69,71,72,89,102,112], five studies used non-resorbable membranes [53,54,56,57,119], and three studies combined resorbable and non-resorbable membranes [55,70,114].…”
Section: Animal Class II Furcation Defects Treated With Ofd and Gtrmentioning
confidence: 99%